1998
DOI: 10.1038/sj.gt.3300709
|View full text |Cite
|
Sign up to set email alerts
|

Decorin gene transfer-mediated suppression of TGF-β synthesis abrogates experimental malignant glioma growth in vivo

Abstract: Cytokines such as transforming growth factor-beta (TGF-beta) are thought to mediate escape from immune surveillance in human malignant glioma. Here, we report that ectopic expression of the small TGF-beta-binding proteoglycan, decorin, inhibits not only TGF-beta bioactivity but also TGF-beta 1 and TGF-beta 2 mRNA transcription and TGF-beta protein synthesis by human LN-18, LN-229, T98G and rat C6 glioma cells in vitro. Ectopic expression of decorin in C6 rat glioma cells results in strong inhibition of tumor f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0
7

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(99 citation statements)
references
References 24 publications
3
89
0
7
Order By: Relevance
“…The improved survival in Lewis rats that received decorin-transfected CNS-1 cells, is similar to results obtained in tumor xenografts and in the C6 glioma model using C6 cells expressing decorin. 11,13 However, in the C6 glioma model decorin expression resulted in tumor regression in 100% of experimental Sprague-Dawley (SD) rats. One of the possible explanations for the increased tumor regression is that because C6 cells are not syngeneic in SD rats, tumor regression by decorin could be enhanced by host versus graft rejection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The improved survival in Lewis rats that received decorin-transfected CNS-1 cells, is similar to results obtained in tumor xenografts and in the C6 glioma model using C6 cells expressing decorin. 11,13 However, in the C6 glioma model decorin expression resulted in tumor regression in 100% of experimental Sprague-Dawley (SD) rats. One of the possible explanations for the increased tumor regression is that because C6 cells are not syngeneic in SD rats, tumor regression by decorin could be enhanced by host versus graft rejection.…”
Section: Discussionmentioning
confidence: 99%
“…4,31,32 Additionally, it has also been shown that decorin inhibits TGF-b mRNA transcription and TGF-b protein synthesis. 13,33 However, these functions appear to be highly cell-type specific. In certain cellular systems, decorin blocks the activity of TGF-b, whereas in others its binding augments the bioactivity of the cytokine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…De modo adicional, el TGF-β2 está implicado en la angiogénesis y en la estimulación del crecimiento tumoral 43 . Apoyando estos datos, existen experimentos con un inhibidor de este factor, la decorina, que han demostrado una supresión del crecimiento tumoral con efecto inmunoestimulador en diferentes estudios in vivo e in vitro 72,95 .…”
Section: Inmunología De Los Astrocitomasunclassified